Analysis Workload And Communication Effects On Employee Performance - Lussianda, Erfa Okta; Adrian, Muhammad; Anggraini, Nia; Fahrozi, Muhammad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
This study investigates the impact of analysis workload and communication on employee performance, focusing on Examination, Collection, Intelligence, and Investigation departments. Using a sample of 42 individuals, data was analyzed through descriptive and inferential statistics, including validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. Findings indicate that while workload does not significantly affect performance, communication does. The combined effect of workload and communication significantly influences performance, explaining 69.1% of its variability. Keywords: Workload, Communication, Performance.